Tunable electronic and optical properties of the MoS2/MoSe2 heterostructure nanotubes. (August 2019) - Wang, Yanzong; Huang, Rui; Kong, Fanjie; Gao, Benling; Li, Guannan; Liang, Feng; Hu, Guang
Abstract: The electronic and optical properties of the MoS2 /MoSe2 heterostructure nanotubes (NTs) with different ratios are systematically investigated by first principles calculations. It is found that the zigzag and armchair MoS2 /MoSe2 heterostructure NTs retain direct and indirect band gap under different MoSe2 ratios, respectively. It is interesting that the band gap of the armchair NTs decreases firstly and then increases with the increase of MoSe2 ratios, while the band gap of the zigzag NTs decreases gradually with the increase of MoSe2 ratios. Moreover, the dielectric function, absorption coefficient, refractive index and reflectivity coefficient of the MoS2 /MoSe2 heterostructure NTs exhibit red shift with the increase of MoSe2 ratios. Especially, the static dielectric constant ε 1 ( 0 ) and static refractive index n ( 0 ) increase monotonously with the increase of MoSe2 ratios. These results suggest that the MoS2 /MoSe2 heterostructure NTs may serve as promising building blocks for optoelectronic nanodevices. Highlights: The band structures of MoS2 /MoSe2 heterostructure nanotubes can be modulated. The variation trends of the band gaps are dependent on chirality. The optical parameters exhibit red shift with the increase of MoSe2 ratios. The static dielectric constant and static refractive index change monotonously.